1990
DOI: 10.1128/mcb.10.5.2437
|View full text |Cite
|
Sign up to set email alerts
|

The ABF1 factor is the transcriptional activator of the L2 ribosomal protein genes in Saccharomyces cerevisiae.

Abstract: The same factor, ABF1, binds to the promoters of the two gene copies (L2A and L2B) coding for the ribosomal protein L2 in Saccharomyces cerevisiae. In vitro binding experiments and in vivo functional analysis showed that the different affinities of the L2A and L2B promoters for the ABF1 factor are responsible for the differential transcriptional activities of the two gene copies. The presence of ABF1-binding sites in front of many housekeeping genes suggests a general role for ABF1 in the regulation of gene ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Abf1 was assigned to the first split and was determined to control genes that were downregulated early on. This agrees with previous studies that implicated Abf1 in being involved in regulating the ribosome (Della Seta et al , 1990; Planta 1997). Two G1 cell‐cycle activators, Swi4 and Mbp1, now appear on a split starting at the 2‐h point on the recovery path.…”
Section: Resultssupporting
confidence: 94%
“…Abf1 was assigned to the first split and was determined to control genes that were downregulated early on. This agrees with previous studies that implicated Abf1 in being involved in regulating the ribosome (Della Seta et al , 1990; Planta 1997). Two G1 cell‐cycle activators, Swi4 and Mbp1, now appear on a split starting at the 2‐h point on the recovery path.…”
Section: Resultssupporting
confidence: 94%
“…Northern analysis showed that PRO3 mRNA levels decreased considerably after 1 h at 37°C in the ts mutants both in the background of full-length and the C-terminal deletion of Abf1, but not in the corresponding wild-type strains (Figure 5B). In contrast, neither QCR8 nor TCM1/RPL3 , both of which depend on Abf1 binding sites for transcription (39,40), showed significantly decreased transcript levels at 37°C in either abf1-1 mutant, consistent with previous work (10), nor in the abf1(1–592) ts mutant (Figure 5B). Similar results were also seen with SPT15 and RPS28A (data not shown), both of which rely on Abf1 binding sites for their expression [(10) and Figure 3B].…”
Section: Resultssupporting
confidence: 91%
“…Fewer promoters that are likely to bind Rap1 but that are not affected by loss of Rap1 binding were identified than for Abf1, and none have thus far been verified by mutagenesis of Rap1 binding sites, as has been done for Abf1 (3740). Promoters known to depend on Rap1 binding sites, such as HIS4 and many RP gene promoters (3,28) show decreased transcription in our microarray experiments, suggesting that at least most promoters that depend on Rap1 binding sites for full expression also require continued Rap1 binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear import not only plays a pivotal role in ensuring the function of nuclear proteins at their desired subcellular location, but also provides an important mechanism by which the activities of these proteins are regulated in response to changes in physiological conditions. Given the constitutive presence of Abf1p at ARS1 throughout the cell cycle (35), as well as its relatively high abundance (10,36), CS1 may simply function to sustain a constitutive presence of the protein in the nucleus. However, it remains possible that under certain conditions the nuclear function of Abf1p may be modulated through masking the NLS activity of CS1.…”
Section: Discussionmentioning
confidence: 99%